2023
DOI: 10.3390/antibiotics12010144
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Impact of Bacterial Infections and the Associated Mortality Predictors in Patients with COVID-19 Admitted to a Tertiary Center from Eastern Europe

Abstract: 1. Background: Literature data on bacterial infections and their impact on the mortality rates of COVID-19 patients from Romania are scarce, while worldwide reports are contrasting. 2. Materials and Methods: We conducted a unicentric retrospective observational study that included 280 patients with SARS-CoV-2 infection, on whom we performed various microbiological determinations. Based on the administration or not of the antibiotic treatment, we divided the patients into two groups. First, we sought to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Regarding inflammatory status, studies have shown increased proinflammatory markers in the serum of COVID-19 patients [43][44][45][46]. In CDI, CRP levels can predict severity [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding inflammatory status, studies have shown increased proinflammatory markers in the serum of COVID-19 patients [43][44][45][46]. In CDI, CRP levels can predict severity [47,48].…”
Section: Discussionmentioning
confidence: 99%